Assessment of Brazilian hospital and healthcare service infrastructure for cleft lip and palate patients - Raquel Souto Silva; Rosa Núbia Vieira de Moura; Daniele Lopes Leal; Soraia Macari; Marcos Azeredo Furquim Werneck; Rafaela da Silveira Pinto (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract: Cleft lip and palate (CLP) represent the most frequently reported congenital anomaly affecting the craniofacial region. The aim of this study was to assess the output (in number of procedures) of the Brazilian hospitals accredited for the treatment of CLP patients, examine the referral flow of patients requiring this type of care, and ascertain the adequacy of the corresponding infrastructure of these healthcare facilities. Methodologically, the study used an observational, cross-sectional, and ecological design. Output data, categorized by state and macro-region, and patient referral flow records were accessible through the Outpatient Information System (SIA, in its Portuguese acronym) and the Hospital Information System (SIH, in Portuguese), respectively. Infrastructure assessment relied on data sourced from the National Register of Health Establishments (CNES, in Portuguese). Analysis encompassed data from 28 accredited hospitals. Concerning output metrics, the state of São Paulo ranked first in the number of procedures conducted. The establishments exhibiting the lowest output performance comprised six hospitals located in the Southeast region and two in the Center-West region. Examination of patient referral flow corroborated the concentration of procedures predominantly conducted in the Southeast, notably within São Paulo state. Infrastructure evaluation encompassed the following categories: physical facilities, diagnostic and therapeutic support services, equipment, and comprehensive multidisciplinary care services. The data showed that roughly 61% of the hospitals surveyed possessed less than half of the recommended items. The primary deficiency identified pertained to inadequacies in equipment availability. Conversely, the best outcomes were associated with diagnostic and therapeutic support services. It was concluded that enhancing hospital infrastructure is imperative for the amelioration of care provision to patients with CLP across all Brazilian states.